Morphological and Microscopical Characteristics of Murdannia bracteata (C.B.Clarke) J.K.Morton ex D.Y.Hong - Duc Loi, Vu; Thi Thanh Huong, Do; Hong Duong, Le; Xuan Tung, Nguyen; Thuc Thu Huong, Nguyen; Truong, Pham Van (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Morphological and microscopical characteristics of “Co ruoi la bac” collected in Nam Dinh province were studied. Results have identified the scientific name of the plant as Murdannia bracteata (family Commelinaceae). Besides, the microscopical characteristics and powder microscopy of leaf and stem of M. bracteata species were established. Specifically, the plant’s leaf and stem are characterized by pale violet corolla, oval bracts and needle shape calcium oxalate crystals converging or single in the soft tissue of the leaf; the herbal powder has twisted vascular grafts, unicellular hairs,… Keywords: Murdannia bracteata , M. bracteata , Murdannia bracteata (C.B.Clarke) J.K.Morton ex D.Y.Hong, Commelinaceae, morphological characteristics, microscopical characteristic References [1] M. D. O. Pellegrini, R. B. Faden, R. F. D. Almeida, Taxonomic Revision of Neotropical Murdannia Royle (Commelinaceae), PhytoKeys, Vol. 74, 2016, pp. 35-78, https://doi.org/10.3897/phytokeys.74.9835. [2] R. B. Faden, K. E. Inman, Leaf Anatomy of The African Genera of Commelinaceae: Anthericopsis and Murdannia, The Biodiversity of African Plants, 1996, pp. 464-471, https://doi.org/10.1007/978-94-009-0285-558. [3] M. C. Naik, B. R. P. Rao, A New Species of Dewflower Murdannia Sanjappae (Commelinaceae) from Andaman Islands, India, Journal of Threatened Taxa, Vol. 9, No. 11, 2017, pp. 10909-10913, http://doi.org/10.11609/jott.3341.9.11.10909-10913. [4] V. V. Chi, Dictionary of Medicinal Plants in Vietnam, Medical Publishing House, Hanoi, 2012 (in Vietnamese). [5] P. H. Ho, An Illustrated Flora of Vietnam, Youth Publishing House, Ho Chi Minh City, 2003 (in Vietnamese). [6] M. Betti, A. Minelli, B. Canonico, P. Castaldo, S. Magi, M. Aisa, F. Galli, Antiproliferative Effects of Tocopherols (Vitamin E) on Murine Glioma C6 Cells: Homologue-specific Control of PKC/ERK and Cyclin Signaling, Free Radical Biology and Medicine, Vol. 41, No. 3, 2006, pp. 464-472, http://doi.org/10.1016/j.freeradbiomed.2006.04.012. [7] N. N. Thin, Plant Research Methods, Education Publishing House, Hanoi, 2006 (in Vietnamese). [8] V. D. Loi, L. T. T. Huong, Texbook: Practical Botany - Pharmacognosy - Traditional Medicine, Hanoi National University Publishing House, Hanoi, 2017 (in Vietnamese).